PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS STEM PADA MATA PELAJARAN MATEMATIKA DI KELAS IV SEKOLAH DASAR - Ayu Latifa, Dwi; Rayendra; Felicita Amsal, Mutiara; Kurnia, Reni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a STEM-based interactive multimedia product for mathematics, including Equivalent Fractions, at SDN 11 Lubuk Buaya, Padang. The main problem is the low mathematics learning outcomes due to the continued use of conventional notes and the lack of interactive multimedia. The research method used is Research and Development (R&D) with a 4D development model (Define, Design, Development, and Disseminate). The research subjects consisted of a material expert validator, two media expert validators, and fourth-grade students at SDN 11 Lubuk Buaya, Padang. The research instrument used a validity and practicality questionnaire. The results showed that the validity test by the material expert was 97.64%, categorized as very valid, the validity test by the media expert was 96.95%, categorized as very valid, and the practicality test was 97.60%, categorized as very practical. Based on the results of the validity and practicality tests, it can be concluded that STEM-based interactive multimedia in mathematics in fourth-grade elementary school is valid and practical for use in learning.